Tenaga Kerja Wanita (TKW) Dan Interseksionalitas Gender Dalam Dinamika Keluarga - Akh. Syamsul Muniri; Nur Shofa Ulfiyati (Institut Agama Islam Miftahul Ulum Pamekasan, 2026)
In the current industrial era, female workers seem to be the driving force of family economic development, as evidenced by the tendency for women to participate in the workforce abroad. Referring to the rights and obligations of husbands and wives, gender discrimination exists, as migrant workers working abroad are often encouraged and ordered by their husbands, despite the fact that in families, the husband, as head of the household, must work hard to meet the family's economic needs. Their income is sent to their husbands for daily needs, including clothing, food, education, health care, and home infrastructure. The purpose of this study is to demonstrate that gender discrimination in employment occurs within the family environment. The research method used by the researcher in this case is a qualitative descriptive approach. Data sources were obtained from several cases in journals and research results. Data analysis techniques used qualitative research in the form of data reduction and data display. Based on the results of the study, it can be concluded that migrant workers working abroad must be of their own free will without coercion from anyone. In addition, families must consider the positive and negative impacts on family life. The positive impacts include increased family income, the fulfillment of daily needs, and the possession of substantial assets, which ultimately improves the family's standard of living. Negative impacts include infidelity, less harmonious family relationships, less than optimal children's education, and financial management that focuses solely on consumption.